The challenges of developing the Saudi Sukuk market in line with objectives of Vision 2030 - Alnagar, Ahmed Mohamed Hassan; Othman, Anwar Hasan Abdullah; Mohd Noor, Azman; Zakariyah, Habeebullah (Springer International Publishing, 2021)
The paper aim to explore the impact of five challenges on the development of sukuk issuances market in the Kingdom in line with the financial sector development plans within vision 2030 objectives. The study adopted quantitative method by distributing a questionnaire to 115 experts involved in the Saudi sukuk market. The results have been analyzed by Smart PLS 3, and it showed a statistically significant effect on the relationship between the five challenges and the sukuk market development in the Kingdom. At the level of sub-challenges, the results have showed that there was no statistically significant impact between the legal framework regulating sukuk issuance in the Kingdom and sukuk market development. While there was a statistically significant impact of the other four challenges on sukuk market development, namely: (1) Shari’ah governance, (2) secondary market activation, (3) the credit rating (4) yield curve. The research has recommended setting a mandatory framework of Shari’ah governance for sukuk issuance, allowance to retail investors for trading in sukuk, requiring sukuk issuers to credit rating the local sukuk issuance, and finally announcement of the yield curve on Saudi government sukuk and considering it as a benchmark pricing index.